Cytogenetics of warrior wasps (Vespidae: Synoeca) reveals intense evolutionary dynamics of ribosomal DNA clusters and an unprecedented number of microchromosomes in Hymenoptera - Menezes, Rodolpho S.T.; Gazoni, Thiago [UNESP]; Costa, Marco A. (Oxford University Press (OUP), 2019)
Chromosomal regions enriched in repetitive DNA sequences have a predisposition to instability, resulting in a propensity to undergo structural rearrangements. Hence, the rRNA multigene family, a type of tandem repeat sequences, is a valuable cytogenetic marker for studying genomic organization and chromosomal differentiation. To investigate whether the evolutionary dynamics of heterochromatin and rDNA clusters played a role in the genomic reorganization and chromosomal evolution of a social wasp genus, we used the C-banding technique and fluorescence in situ hybridization (FISH) to conduct chromosomal mapping of the major rDNA class in three closely related species of warrior wasps: Synoeca cyanea, S. ilheensis and S. surinama. In this study, the S. surinama karyotype is reported for the first time. It contains 2n = 34 regular-sized chromosomes and approximately 30 microchromosomes, thus representing an unprecedented number of this chromosomal type for the order Hymenoptera. We discuss the putative evolutionary mechanism for the origin of microchromosomes in S. surinama. For the three species, C-positive heterochromatic blocks were predominantly detected in the pericentromeric region of all chromosomes. However, our FISH results revealed striking variability in the number and chromosomal position of rDNA clusters among the three species studied, as well as intraspecific variations in S. cyanea and S. ilheensis, which suggests intense evolutionary dynamics of this repetitive DNA family and highlights rapid chromosomal evolution in these insects.
Keywords: Chromosomal evolution; Molecular cytogenetics; rDNA; social wasps; Vespidae